'On of the princypalle havenes of the see': The port of Famagusta and the ship graffiti in the Church of St George of the Greeks, Cyprus - Walsh, Michael J. K. (Wiley, 2008)
In its 1000-year history the port has been the source of triumph and tragedy for the city of Famagusta, being the conduit through which flowed both enormous wealth and destruction. Today the French medieval and Greek Orthodox churches, and the Venetian walls, though ruined, still carry physical traces of this turbulent society in the form of ship graffiti. Though such images are often classified as 'low-art', they are nevertheless imbued with a deep social significance, which the maritime historian can yet use to get a glimpse of an important, though virtually-forgotten, heritage in the Eastern Mediterranean. (C) 2007 The Author.
Keywords: Cyprus; Famagusta; ship graffiti; Gothic; maritime